ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DALAM UPAYA EFISIENSI BIAYA PERSEDIAAN PADA PT. IRMA JAYA RUBBER (IJR) - Christin Agustian, - (2011)
This study examines the phenomenon of the PT. Irma Jaya Rubber (IJR), namely the presence of raw material shortages and excess raw material. The purpose of this study is to investigate, study and describe the raw material inventory control systems are implemented and cost efficiency of inventory on the company. In this research using descriptive method with quantitative approach. Sources of data used is the purchase, use, purchase costs, ordering costs, storage costs and raw material cost budgets Fourth Quarter of 2010. Technical analysis of the data used is economical ordering EOQ method. Raw material inventory control system of the company is currently based on the needs of natural raw rubber raw materials every month and do not provide safety stock and the limit to be able to place an order again (reorder point). The cost efficiency of inventory according to the company's policy is at the level of efficiency in October and November, as well as on the efficient level in December. By using the EOQ method demonstrated at the level of efficiency of each month. Suggestions author is a company should review the policy of raw material inventory, inventory control system of the company today should not be set again and replaced with the EOQ method, companies should determine the amount of safety stock and reorder.